2019
DOI: 10.1002/ajh.25395
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of myeloablative and reduced‐intensity conditioning allogeneic hematopoietic cell transplantation for therapy‐related acute myeloid leukemia with prior solid tumor: A report from the acute leukemia working party of the European society for blood and bone marrow transplantation

Abstract: Therapy‐related acute myeloid leukemia (t‐AML) arises as a late complication following antecedent solid tumors or hematologic diseases and their associated treatments. There are limited data regarding risk factors and outcomes following allogeneic hematopoietic cell transplantation (HCT) for t‐AML following a prior solid tumor, and furthermore, the impact of myeloablative (MAC) vs reduced‐intensity conditioning (RIC) on survival is unknown. The acute leukemia working party (ALWP) of the European society for bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
4
12
0
Order By: Relevance
“…In our study, clofarabine and treosulfan were associated with a low incidence of severe hepatic toxicities, such as VOD. The NRM was 18% at 1 year, comparable to that reported for other myeloablative conditioning regimens in high-risk populations [35]. Although in line with our primary endpoint, recently a lower incidence of NRM was reported for patients in CR using a combination of busulfan and fludarabine [25].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, clofarabine and treosulfan were associated with a low incidence of severe hepatic toxicities, such as VOD. The NRM was 18% at 1 year, comparable to that reported for other myeloablative conditioning regimens in high-risk populations [35]. Although in line with our primary endpoint, recently a lower incidence of NRM was reported for patients in CR using a combination of busulfan and fludarabine [25].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the results may contribute to the design of optimized transplant protocols. Previous studies have suggested comparable outcomes after RIC and MAC in sAML, however, with a trend for better outcome after MAC 11,29 . Hence, a myeloablative, but reduced toxicity conditioning regimen such as the combination of Fludarabine and Treosulfan 30 might be of particular value in patients with sAML.…”
Section: Discussionmentioning
confidence: 87%
“…As a consequence of the low cure rates of not more than 20% after chemotherapy alone [8,9], allogeneic HSCT often is the preferred consolidation option in s/tAML patients. Here, mostly registrybased data not including de novo AML individuals suggest allogeneic HSCT as a suitable and often curative treatment option for s/tAML patients [13][14][15][16][17][18]. However, data comparing outcomes of s/tAML and de novo AML patients undergoing allogeneic HSCT remain sparse.…”
Section: Introductionmentioning
confidence: 99%